At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the midpoint of the [tex]\( x \)[/tex]-intercepts of the function [tex]\( f(x) = (x-2)(x-4) \)[/tex], follow these steps:
1. Identify the [tex]\( x \)[/tex]-intercepts of the function:
The [tex]\( x \)[/tex]-intercepts occur where the function [tex]\( f(x) \)[/tex] equals zero. Set [tex]\( f(x) = 0 \)[/tex] and solve for [tex]\( x \)[/tex]:
[tex]\[ (x-2)(x-4) = 0 \][/tex]
This equation is satisfied when either [tex]\( x-2 = 0 \)[/tex] or [tex]\( x-4 = 0 \)[/tex].
Solving these equations:
[tex]\[ x - 2 = 0 \implies x = 2 \][/tex]
[tex]\[ x - 4 = 0 \implies x = 4 \][/tex]
So, the [tex]\( x \)[/tex]-intercepts are [tex]\( x = 2 \)[/tex] and [tex]\( x = 4 \)[/tex].
2. Find the midpoint of these intercepts:
The midpoint of two points [tex]\( (x_1, 0) \)[/tex] and [tex]\( (x_2, 0) \)[/tex] can be found using the midpoint formula for the [tex]\( x \)[/tex]-coordinates:
[tex]\[ \text{Midpoint} = \left( \frac{x_1 + x_2}{2}, 0 \right) \][/tex]
Substitute the values of [tex]\( x_1 \)[/tex] and [tex]\( x_2 \)[/tex]:
[tex]\[ x_1 = 2, \quad x_2 = 4 \][/tex]
[tex]\[ \text{Midpoint} = \left( \frac{2 + 4}{2}, 0 \right) = \left( \frac{6}{2}, 0 \right) = (3, 0) \][/tex]
Therefore, the midpoint of the [tex]\( x \)[/tex]-intercepts of the function [tex]\( f(x) = (x-2)(x-4) \)[/tex] is [tex]\( \boxed{(3, 0)} \)[/tex].
1. Identify the [tex]\( x \)[/tex]-intercepts of the function:
The [tex]\( x \)[/tex]-intercepts occur where the function [tex]\( f(x) \)[/tex] equals zero. Set [tex]\( f(x) = 0 \)[/tex] and solve for [tex]\( x \)[/tex]:
[tex]\[ (x-2)(x-4) = 0 \][/tex]
This equation is satisfied when either [tex]\( x-2 = 0 \)[/tex] or [tex]\( x-4 = 0 \)[/tex].
Solving these equations:
[tex]\[ x - 2 = 0 \implies x = 2 \][/tex]
[tex]\[ x - 4 = 0 \implies x = 4 \][/tex]
So, the [tex]\( x \)[/tex]-intercepts are [tex]\( x = 2 \)[/tex] and [tex]\( x = 4 \)[/tex].
2. Find the midpoint of these intercepts:
The midpoint of two points [tex]\( (x_1, 0) \)[/tex] and [tex]\( (x_2, 0) \)[/tex] can be found using the midpoint formula for the [tex]\( x \)[/tex]-coordinates:
[tex]\[ \text{Midpoint} = \left( \frac{x_1 + x_2}{2}, 0 \right) \][/tex]
Substitute the values of [tex]\( x_1 \)[/tex] and [tex]\( x_2 \)[/tex]:
[tex]\[ x_1 = 2, \quad x_2 = 4 \][/tex]
[tex]\[ \text{Midpoint} = \left( \frac{2 + 4}{2}, 0 \right) = \left( \frac{6}{2}, 0 \right) = (3, 0) \][/tex]
Therefore, the midpoint of the [tex]\( x \)[/tex]-intercepts of the function [tex]\( f(x) = (x-2)(x-4) \)[/tex] is [tex]\( \boxed{(3, 0)} \)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.